2021
DOI: 10.3390/ijms23010069
|View full text |Cite
|
Sign up to set email alerts
|

Galectins in Early Pregnancy and Pregnancy-Associated Pathologies

Abstract: Galectins are a family of conserved soluble proteins defined by an affinity for β-galactoside structures present on various glycoconjugates. Over the past few decades, galectins have been recognized as important factors for successful implantation and maintenance of pregnancy. An increasing number of studies have demonstrated their involvement in trophoblast cell function and placental development. In addition, several lines of evidence suggest their important roles in feto-maternal immune tolerance regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 151 publications
(291 reference statements)
0
8
0
Order By: Relevance
“…Moreover, Gal-13 and Gal-14 potentially regulate placental development through their induction of angiogenesis at the fetal-maternal interface [85]. Placental galectins also play a crucial role in regulating the mother's immune tolerance toward embedded embryos, and alterations in their expression levels are significantly associated with abnormal pregnancy and infertility [86, 87]. Gal-13 induces apoptosis of activated T cells in vitro, redirects and eliminates T cells and macrophages in the maternal decidua, and polarizes neutrophils toward a permissive phenotype for placental growth [46, 88].…”
Section: Functional Aspects Of Placental Galectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gal-13 and Gal-14 potentially regulate placental development through their induction of angiogenesis at the fetal-maternal interface [85]. Placental galectins also play a crucial role in regulating the mother's immune tolerance toward embedded embryos, and alterations in their expression levels are significantly associated with abnormal pregnancy and infertility [86, 87]. Gal-13 induces apoptosis of activated T cells in vitro, redirects and eliminates T cells and macrophages in the maternal decidua, and polarizes neutrophils toward a permissive phenotype for placental growth [46, 88].…”
Section: Functional Aspects Of Placental Galectinsmentioning
confidence: 99%
“…Aberrant expression of placental galectins is associated with various pathologies, including GDM, PE, IUGR, and HELLP syndrome [86]. Gal-13, Gal-14, and Gal-16 are abundantly expressed in normal gestational placental tissue, with syncytiotrophoblast cells serving as the primary site of synthesis [43, 91].…”
Section: Functional Aspects Of Placental Galectinsmentioning
confidence: 99%
“…An intricate chemical chain reaction, which is controlled by endocrine, paracrine and autocrine regulators present in both the embryo and the mother, is essential to the progression of embryo implantation [ 92 ]. The results of in vitro and in vivo studies have demonstrated that galectins are crucial mediators in the implantation process [ 93 ]. During embryo implantation, the enhanced expression of gal-1, -3 and -9 in endometrial epithelial cells reflect the galectins’ most crucial involvement in endometrial receptivity.…”
Section: The Role Of Galectins In the Maternal–fetal Interfacementioning
confidence: 99%
“…21 In recent years, galectins have been identified as potential contributors to a variety of reproductive processes, such as blastocyst implantation, feto-maternal immunological tolerance, placental development, and angiogenesis. 22 Despite the fact that galectin functions are important determinants of healthy pregnancies, 23 galectins also play critical role in several pregnancy complications such as preeclampsia, 24,25 recurrent spontaneous abortion, 26 ectopic pregnancy, 27 endometriosis. 28 Galectins are considered as the potential regulators of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Galectins are emerged as regulators of cell growth, proliferation, differentiation, apoptosis, signal transduction, mRNA splicing and interactions with the extracellular matrix 17 and involved in several diseases like cancer, 18 cardiovascular disease, 19 kidney disease 20 and lung disease 21 . In recent years, galectins have been identified as potential contributors to a variety of reproductive processes, such as blastocyst implantation, feto‐maternal immunological tolerance, placental development, and angiogenesis 22 . Despite the fact that galectin functions are important determinants of healthy pregnancies, 23 galectins also play critical role in several pregnancy complications such as preeclampsia, 24,25 recurrent spontaneous abortion, 26 ectopic pregnancy, 27 endometriosis 28 .…”
Section: Introductionmentioning
confidence: 99%